Ultraviolet-induced fluorescent imaging for millipede taxonomy - Paul Marek (Research Ideas and Outcomes, 2017)
Fluorescent imaging has been traditionally applied to cell biology, and more recently to entomology to capture microscopic images of insect anatomy. However, the technique has not been applied to the study of millipedes, most of which autofluoresce as a result of endogenous fluorescent molecules in their cuticle such as pterins and coproporphyrins. This study compares commercially available ultraviolet light sources for fluorescent photography of millipedes for the documentation of anatomical structures. Millipedes that were most strongly fluorescent were those in the order Polydesmida, and produced the brightest fluorescence that was most easily photographed using this technique. However, millipedes of the orders Spirobolida and Siphonophorida were also fluorescent and produced a bright blue visible emission. The best quality images were those obtained with a modified flash that produced the highest intensity and shortest wavelength ultraviolet light.